Developing idle Waqf (endowment) lands through cooperative-Waqf model: the case of Malaysia - Allah Pitchay, Anwar; Azhar, Zubir; Mohd Thas Thaker, Mohamed Asmy; Mydin, Al Amin (2017)
Purpose – This paper attempt to offer an alternative mode of financing for developing idle Waqf land using cooperative and Waqf. Design/Methodology/Approach – The present study evaluated relevant existing literatures on the; (i) issues of financing faced by Waqf institution in developing idle Waqf lands, and (2) existing models of cash Waqf have been reviewed and based on this gap, we proposed a hybrid model of Cooperative-Waqf. Findings – The proposed model is unique due to the new dimension which is membership is embedded into the Waqf project. This means the donors are given privilege to received benefit from the commercialise project which is develop on the Waqf lands. So far, the existing models of cash Waqf are using traditional method which means the donors only contribute cash Waqf and they do not aware about the utilisation of the cash Waqf. Commonly, this agency problem is occurred due to the lack of two-way communication between cash Waqf donors and Waqf institution. Therefore, the proposed model is able to boost more participation to develop Waqf land and also create harmonisation relationship between cash Waqf donor and Waqf institution. Research limitation/Implication – The paper is based on conceptual explorations of existing literatures in the area of Waqf and cash Waqf, and the finding is not empirically investigated. Practical Implication – The proposed hybrid model in this study will provide an alternative way of boosting cash Waqf and develop Waqf lands. This model is significant to policy maker such as government, private and NGOs to promote philanthropy based development. Originality/Value – The present study extent the existing literatures in area of Waqf and cash Waqf models especially the practise of this instrument in the context of Malaysia. Besides the literature, the present also offers new hybrid model which currently are not practised in any Muslim and minority Muslim countries.